1976
DOI: 10.1111/j.1469-7998.1976.tb02275.x
|View full text |Cite
|
Sign up to set email alerts
|

Locomotion, pedal retraction and extension, and the hydraulic systems of Bullia (Gastropoda: Nassaridae)

Abstract: Surface locomotion and burrowing by Bullia digitalis have been analysed by use of ciné film and electronic recording. Both movements are shown to be carried out by a series of steps in which the propodium is first extended whilst the snail is anchored by the posterior of the foot (penetration anchor) and, when buried, also by the shell; secondly the shell is drawn forwards and downwards towards the anchored propodium (terminal anchor). The extremely flattened foot of this snail contains a greatly enlarged peda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Unlike most of the other sand-burying gastropods considered here, nassariids have a large, powerful foot, enabling them to bury rapidly (Trueman & Brown, 1976, 1992aVermeij & Zipser, 1986;Savazzi, 1989Savazzi, , 1994Trueman & Hodgson, 1990). In keeping with the trade-off between foot size and streamlining, most nassariids are less streamlined than most sand-buriers in the other clades examined (Fig.…”
Section: Nassariidaementioning
confidence: 67%
“…Unlike most of the other sand-burying gastropods considered here, nassariids have a large, powerful foot, enabling them to bury rapidly (Trueman & Brown, 1976, 1992aVermeij & Zipser, 1986;Savazzi, 1989Savazzi, , 1994Trueman & Hodgson, 1990). In keeping with the trade-off between foot size and streamlining, most nassariids are less streamlined than most sand-buriers in the other clades examined (Fig.…”
Section: Nassariidaementioning
confidence: 67%
“…16). Bullia digitalis, Bullia rhodostoma , Hydrobia ulvae , Littorina littorea , Lunatia heros and Polinices duplicatus produce trails with lateral ridges and transverse bars (Raymond 1922; Abel 1935; Häntzschel 1938; Gräff 1956; Brown 1971; Schäfer 1972; Trueman and Brown 1976; Knox and Miller 1985).…”
Section: Affininties Of the Producermentioning
confidence: 99%
“…The absence of any fluid-filled cavities in these sections suggests that antagonism occurs directly between sets of muscle fibres, as in other muscular antagonistic systems, e.g. the columellar muscle of Bullia (Trueman & Brown, 1976) and of other gastropods (Brown & Trueman, 1982).…”
Section: Experimental Observationsmentioning
confidence: 87%
“…Examination of sections of the columellar muscle of the latter species showed that the muscle consisted of a three dimensional network of closely associated fibres, in which the principal or retractor fibres had their long axes parallel to the length of the muscle, while the others were arranged transversely to this ( Fig. 5(c)) (Trueman & Brown, 1976). Contraction of these latter fibres compresses the longitudinal fibres and so brings about their extension.…”
mentioning
confidence: 99%
See 1 more Smart Citation